The compositional portrayal of narrative structure in adventure video games: a study of the creative approaches in GRIS - Loubser, Micaela Megan Nolukholo (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMus)--Stellenbosch University, 2025.